Comparative efficiency of continuous trainings and aerobic interval training in patients after myocardial infarction. (25th November 2020) - Dovgalyuk, Y; Chistyakova, Y.U.V; Jarchenkova, L.L; Fokicheva, S.O; Zolotareva, A.A; Vorobyeva, T.V; Kozlova, M.V; Mishina, I.E
Abstract: Background: The basis of cardiac rehabilitation programs (CRP) is aerobic physical training, which improves exercise capacity in patients with an acute myocardial infarction (MI) after primary angioplasty of the infarct-related vessel. However, which type - aerobic interval training (AIT) or aerobic continuous trainings (ACT) are most effective for improving peak oxygen uptake (VO2 max) remains unclear and controversial. Purpose: To evaluate the effects of CRP, including AIT or ACT, on exercise capacity and lung function in patients with MI after primary angioplasty of the infarct-related vessel. Methods: Seventy MI patients (58 men and 12 women, mean age – 59, 2±8, 0 years) were undergone the three-week CRP in the Ivanovo State Medical Academy Clinic. The CRP for all patients included: daily controlled physical training on the Bicycle Ergometer and Treadmill, group exercises in therapeutic gymnastics, dosed walking and walking on the stairs with an individually calculated pace. Depending on the mode of physical training all patients were randomized of five weekly sessions in to two groups, comparable in age and gender: AIT group (35 patients) and ACT group (35 patients). The ACT group was training at 50–60% of peak heart rate. The AIT group protocol consisted of ten 1-min intervals at 85–90% of maximal heart rate separated by ten 1-min active recovery periods of moderate intensity at 40–60% of the maximal heart rate. Changes in 6-min walk distance test (6MWT), peak oxygen uptake (VO2max), relative load power, total lung capacity (TLC) and forced expiratory volume in one second (FEV1) before and after CRP were investigated. Data are presented as a median (interquartile ratio [Q1; Q3]). Results: After finishing CRP 6MWT distance increased in both groups, but was higher in AIT group 492 [460–510] m compared to the ACT group – 465 [424–510] m (p<0.05). Peak oxygen uptake increased more (p<0.05) after AIT: from 16.8 [15.3–19.8] to 20.7 [16.5–21.9] ml kg –1 min –1 (p<0.05), than after ACT – from 15.8 [14.7–18.6] to 16.1 [15.8–20.5] ml kg –1 min –1 (p>0.05). At the end of the CRP relative load power during cardiopulmonary exercise test was higher in AIT group compared to the ACT group: 1.5 [1.3–1.7] vs 1.2 [1.0–1.5] Wt/kg respectively (p<0.05). In the AIT group TLC increased significantly from 3.13 [2.63–4.05] to 4.14 [3.91–4.87] L (p<0.05) then in ACT group: from 3.19 [2.82–3.74] to 3.21 [3.03–3.57] L (p>0.05). FEV1 had no changes in both groups. Both programs reduced anxiety and depression, systolic and diastolic blood pressure and increased quality of life. Conclusion: AIT as compared to ACT provided a more pronounced training effect on the cardiorespiratory system due to high-intensity loading phases. Therefore, AIT is more preferable in cardiac rehabilitation of patients with MI after primary angioplasty of the infarct-related vessel. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Ivanovo State Medical Academy